2018
DOI: 10.1183/13993003.00230-2018
|View full text |Cite|
|
Sign up to set email alerts
|

Safety of nintedanib added to pirfenidone treatment for idiopathic pulmonary fibrosis

Abstract: We assessed safety and tolerability of treatment with pirfenidone (1602–2403 mg·day−1) and nintedanib (200–300 mg·day−1) in patients with idiopathic pulmonary fibrosis (IPF).This 24-week, single-arm, open-label, phase IV study (ClinicalTrials.gov identifier NCT02598193) enrolled patients with IPF with forced vital capacity % pred ≥50% and diffusing capacity of the lung for carbon monoxide % pred ≥30%. Before initiating nintedanib, patients had received pirfenidone for ≥16 weeks and tolerated a stable dose of ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 24 publications
8
80
0
1
Order By: Relevance
“…Overall, our observations support the inclusion of patients with more advanced lung function impairment in future IPF trials investigating novel therapies, as well as combination antifibrotic therapy [28,29]. Whether patients with even greater lung function impairment than those included in this analysis should be included in future clinical trials is open to speculation, but it is certainly a concept for further investigation.…”
Section: Discussionsupporting
confidence: 64%
“…Overall, our observations support the inclusion of patients with more advanced lung function impairment in future IPF trials investigating novel therapies, as well as combination antifibrotic therapy [28,29]. Whether patients with even greater lung function impairment than those included in this analysis should be included in future clinical trials is open to speculation, but it is certainly a concept for further investigation.…”
Section: Discussionsupporting
confidence: 64%
“…The necessity of exerting pharmacological action on different profibrotic signalling pathways as a result of the multifactorial and complex pathogenesis of IPF suggest that better outcomes could be achieved with combination therapy. In recent years, several studies have been published assessing the safety, tolerability and pharmacokinetics of combination therapy with pirfenidone and nintedanib in IPF patients [244][245][246][247]. In a randomised, double-blind phase 2 study conducted in a small group of 50 IPF patients, Ogura et al [30,57] demonstrated that combination therapy with pirfenidone and nintedanib had acceptable safety and tolerability profiles, which was confirmed in other studies [245][246][247].…”
Section: Introductionmentioning
confidence: 79%
“…In recent years, several studies have been published assessing the safety, tolerability and pharmacokinetics of combination therapy with pirfenidone and nintedanib in IPF patients [244][245][246][247]. In a randomised, double-blind phase 2 study conducted in a small group of 50 IPF patients, Ogura et al [30,57] demonstrated that combination therapy with pirfenidone and nintedanib had acceptable safety and tolerability profiles, which was confirmed in other studies [245][246][247]. A Japanese study, however, revealed reduced values of the peak serum plasma concentration and area under the curve (AUC) of nintedanib when it was used simultaneously with pirfenidone [244].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flaherty et al 42 examined the tolerability of pirfenidonenintedanib combination therapy, assessing the occurrence of treatment-emergent adverse events (TEAEs). Of the 89 patients, 78% completed the 24 week single-arm, open label study, with the profile and rate of TEAEs proportionally similar to that of monotherapies.…”
Section: Discussionmentioning
confidence: 99%